(untitled) (Nigerian Journal of Technology, 2008)
The study is an investigation into the effect of rice husk ash (RHA) on some geotechnical properties of a lateritic soil classified as A-2-6 (0) or SW for sub-grade purposes. The investigation includes evaluation of properties such as compaction, consistency limits and strength of the soil with RHA content of 5%, 7.5%, 10% and 12.5% by weight of the dry soil. The results obtained show that the increase in RHA content increased the optimum moisture content but decreased the maximum dry density. It was also observed that increase in RHA content, reduced plasticity and increased volume stability as well as the strength of the soil. 10% RHA content was also observed to be the optimum content.